LncRNA-Disease Association Prediction Using Two-Side Sparse Self-Representation - Ou-Yang, Le; Huang, Jiang; Zhang, Xiao-Fei; Li, Yan-Ran; Sun, Yiwen; He, Shan; Zhu, Zexuan (Frontiers in Genetics, 2019)
Evidences increasingly indicate the involvement of long non-coding RNAs (lncRNAs) in various biological processes. As the mutations and abnormalities of lncRNAs are closely related to the progression of complex diseases, the identification of lncRNA-disease associations has become an important step towards the understanding and treatment of diseases. Since only a limited number of lncRNA-disease associations have been validated, an increasing number of computational approaches have been developed for predicting potential lncRNA-disease associations. However, how to predict potential associations precisely through computational approaches remains challenging. In this study, we propose a novel two-side sparse self-representation (TSSR) algorithm for lncRNA-disease association prediction. By leveraging the self-representations of lncRNAs and diseases learned from known lncRNA-disease associations and the intra-associations among lncRNAs and diseases derived from other existing databases, our method could effectively utilize the learned presentations of lncRNAs and diseases to predict potential associations. The experiment results on three real data sets demonstrate that our TSSR outperforms other competing methods significantly. Moreover, to further evaluate the effectiveness of TSSR in predicting candidate lncRNAs-disease associations, case studies of Melanoma, Glioblastoma and Glioma are carried out in this paper. The results demonstrate that TSSR can effectively identify the lncRNAs associated with these three diseases.